2014
DOI: 10.3389/fpsyt.2014.00133
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Relatively Pure Cannabis Use, but Not Schizotypy, are Associated with Cognitive Attenuations

Abstract: Elevated schizotypy relates to similar cognitive attenuations as seen in psychosis and cannabis/polydrug use. Also, in schizotypal populations cannabis and polydrug (including licit drug) use are enhanced. These cognitive attenuations may therefore either be a behavioral marker of psychotic (-like) symptoms or the consequence of enhanced drug use in schizotypal populations. To elucidate this, we investigated the link between cognitive attenuation and cannabis use in largely pure cannabis users (35) and non-usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Studies in humans have reported inconsistent effects of acute THC (or CB1R agonist) administration on working memory, with different studies reporting impairments (Bedi et al, 2013; D’Souza et al, 2004; Englund et al, 2013; Freeman et al, 2015; Hunault et al, 2009; Lane et al, 2005a; Lile et al, 2014; Morrison et al, 2009; Ramesh et al, 2013; Theunissen et al, 2015; Wesnes et al, 2010), improvements (Makela et al, 2006), or no effects (D’Souza et al, 2008; Kollins et al, 2015; Lile et al, 2011; Ranganathan et al, 2012; reviewed in Broyd et al, 2016). Similar to the mixed effects of acute THC on working memory, studies of chronic cannabis use in humans also report either impairments (Fried et al, 2005; Herzig et al, 2014; Wadsworth et al, 2006) or no effects (Becker et al, 2014; Grant et al, 2012). Furthermore, those who abstained after chronic use showed no difference in performance relative to non-users (Fried et al, 2005), suggesting that after prolonged cannabis use, abstinence can rescue working memory impairments.…”
Section: Discussionmentioning
confidence: 84%
“…Studies in humans have reported inconsistent effects of acute THC (or CB1R agonist) administration on working memory, with different studies reporting impairments (Bedi et al, 2013; D’Souza et al, 2004; Englund et al, 2013; Freeman et al, 2015; Hunault et al, 2009; Lane et al, 2005a; Lile et al, 2014; Morrison et al, 2009; Ramesh et al, 2013; Theunissen et al, 2015; Wesnes et al, 2010), improvements (Makela et al, 2006), or no effects (D’Souza et al, 2008; Kollins et al, 2015; Lile et al, 2011; Ranganathan et al, 2012; reviewed in Broyd et al, 2016). Similar to the mixed effects of acute THC on working memory, studies of chronic cannabis use in humans also report either impairments (Fried et al, 2005; Herzig et al, 2014; Wadsworth et al, 2006) or no effects (Becker et al, 2014; Grant et al, 2012). Furthermore, those who abstained after chronic use showed no difference in performance relative to non-users (Fried et al, 2005), suggesting that after prolonged cannabis use, abstinence can rescue working memory impairments.…”
Section: Discussionmentioning
confidence: 84%
“…Impaired performance may depend on extent of prior exposure, route of administration, dose delivered, and blood cannabinoid concentrations at baseline and after dosing (89). With regard to the chronic effects of cannabis, numerous studies reported null findings in case-control comparisons (46,54,66,81,95,98,110,111), whereas several others found cannabis-related deficits in heavy users (53,78,83,112), including adolescents (113), early-onset but not late-onset adult users (114), and older users (57), and associated with persistent use in a longitudinal study (60). Impaired executive function was evident despite intact performance on other cognitive tasks (48,82) and associated with self-reported problems related to cannabis use (115).…”
Section: Executive Functionmentioning
confidence: 99%
“…Studies that investigate executive components in chronic cannabis users with different patterns of use in working memory (Herzig, Nutt, & Mohr, 2014; Macher & Earleywine, 2012), cognitive flexibility (Hooper, Woolley, & de Bellis, 2014; Scholes & Martin-Iverson, 2010), and inhibitory control (Crane, Schuster, & Gonzalez, 2013; Dougherty et al, 2013) are still inconclusive.…”
mentioning
confidence: 99%